1993
DOI: 10.1172/jci116546
|View full text |Cite
|
Sign up to set email alerts
|

Glycochenodeoxycholate-induced lethal hepatocellular injury in rat hepatocytes. Role of ATP depletion and cytosolic free calcium.

Abstract: Chenodeoxycholate is toxic to hepatocytes, and accumulation of chenodeoxycholate in the liver during cholestasis may potentiate hepatocellular injury. However, the mechanism of hepatocellular injury by chenodeoxycholate remains obscure. Our aim was to determine the mechanism of cytotoxicity by chenode- (Ca,2.) was observed. Removal of extracellular Ca2" abolished the rise in Ca,2., decreased cellular proteolysis, and protected against cell killing by glycochenodeoxycholate. The results suggest that glycocheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
2
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(172 citation statements)
references
References 51 publications
14
153
2
2
Order By: Relevance
“…The fact that conjugation with either glycine or taurine decreased cytotoxicity of CDCA agrees with the observations made by others (Scholmerich et al, 1984). In contrast, Spivey et al (1993) reported that at a concentration of 250 mM, GCDC was more toxic than either CDCA or TCDC. Significant differences in the experimental procedure may explain the discrepancy.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The fact that conjugation with either glycine or taurine decreased cytotoxicity of CDCA agrees with the observations made by others (Scholmerich et al, 1984). In contrast, Spivey et al (1993) reported that at a concentration of 250 mM, GCDC was more toxic than either CDCA or TCDC. Significant differences in the experimental procedure may explain the discrepancy.…”
Section: Resultssupporting
confidence: 90%
“…Significant differences in the experimental procedure may explain the discrepancy. For instance, Spivey et al (1993) worked with hepatocytes after only 2 h in culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spivey et al 2 concluded that the bile salt-induced liver toxicity was due to mitochondrial disfunction, resulting in depleted ATP levels and sustained influx of Ca 2+ leading to hepatocyte necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…that this may be due to the ATP-lowering effect of 2-DG (Foufelle et al 1992). Indeed, lowering of cytosolic ATP/ADP ratios increases cytosolic Ca 2C by inhibiting ATP-dependent pumping into both the extracellular space and intracellular stores (Haworth et al 1987, Spivey et al 1993, Bright et al 1995. The resultant elevation of cytosolic free Ca 2C may then be sufficient to evoke ChREBP nuclear translocation (Noordeen et al 2012) and thus activate the transcription of target genes.…”
Section: Regulation Of Chrebp Activation By Glucosementioning
confidence: 99%